Linha de cuidado em saúde do trabalhador: uma tecnologia para a organização do cuidado ao trabalhador com LER/DORT - Torres, Amélia Romana Almeida (2013)
The present study arose from the need to improve the comprehensiveness of health care workers, especially for workers with repetitive strain injuries and work-related musculoskeletal disorders. So our objective was to build a line of participatory comprehensive care for workers with work-related musculoskeletal disturbance in the SUS from the experience of professionals, managers and integrating the networks of health care. Eveloped in the city of Sobral, this research is a qualitative exploratory type. The action research was the methodology of choice for established itself as a methodology that aims to promote action and the ability to transform reality by the research subjects. Therefore, we used the research group, in a process that led to the formulation, by the subjects involved, the actions considered strategic to offer integral attention to these workers. There is a need of building a care line containing flows and duties of professional care network. We emphasize that these actions care line, were built collectively after four group meetings. The first meeting was to discuss and define the completeness priority actions identified by the group. The second meeting was a workshop that aimed to construct the flow line care, the third meeting a second workshop aimed to define the duties of the professional services that meet the employee and the third and last workshop meeting had as objective to present the flow built by group and validate assignments network of services that meets the employee with repetitive strain injuries and related musculoskeletal disorders work. As a method of treatment of the data we use discourse analysis. The results show that workers with the disease can seek various points of care network, including services emerged Primary Health Care, Specialized Care and Attention to Urgent and Emergency. Merged after the validation of 36 professional assignments.We show that the tasks presented include promotional, preventive, curative, rehabilitative and caregivers. We emphasize that to build a line of thought in need of care worker as the central aspect for your assistance and service flow. Thus, the line care proposal demonstrates a possibility the guarantee of completeness related to the organization of health services, showing the path to be taken by a user, from the Primary Health Care and going through different search services in a range of care required for solve your health problem. For the operation of the line care proposal is necessary to the existence of a shared work among professionals in the Primary Health Care and the other services that have appeared. In this process, as well as construction and agreement of the flow of attention, it is necessary to develop strategies for realizing this path in the network of worker's attention and establish 9 responsibilities and negotiate for safe transfer of care.